De Novo ATP1A1 Variants in an Early-Onset Complex Neurodevelopmental Syndrome. (15th March 2022) - Dohrn, Maike F.; Rebelo, Adriana P.; Srivastava, Siddharth; Cappuccio, Gerarda; Smigiel, Robert; Malhotra, Alka; Basel, Donald; van de Laar, Ingrid; Neuteboom, Rinze Frederik; Aarts-Tesselaar, Coranne; Mahida, Sonal; Brunetti-Pierri, Nicola; et al.
Abstract : ATP1A1 encodes the α1 subunit of the sodium-potassium ATPase, an electrogenic cation pump highly expressed in the nervous system. Pathogenic variants in other subunits of the same ATPase, encoded by ATP1A2 or ATP1A3, are associated with syndromes such as hemiplegic migraine, dystonia, or cerebellar ataxia. Worldwide, only 16 families have been reported carrying pathogenic ATP1A1 variants to date. Associated phenotypes are axonal neuropathies, spastic paraplegia, and hypomagnesemia with seizures and intellectual disability. By whole exome or genome sequencing, we identified 5 heterozygous ATP1A1 variants, c.674A>G;p.Gln225Arg, c.1003G>T;p.Gly335Cys, c.1526G>A;p.Gly509Asp, c.2152G>A;p.Gly718Ser, and c.2768T>A;p.Phe923Tyr, in 5 unrelated children with intellectual disability, spasticity, and peripheral, motor predominant neuropathy. Additional features were sensory loss, sleep disturbances, and seizures. All variants occurred de novo and are absent from control populations (MAF GnomAD = 0). Affecting conserved amino acid residues and constrained regions, all variants have high pathogenicity in silico prediction scores. In HEK cells transfected with ouabain-insensitive ATP1A1 constructs, cell viability was significantly decreased in mutants after 72h treatment with the ATPase inhibitor ouabain, demonstrating loss of ATPase function. Replicating the haploinsufficiency mechanism of disease with a gene-specific assay provides pathogenicity information and increases certainty in variant interpretation. This study further expands the genotype-phenotype spectrum of ATP1A1 .